2019
DOI: 10.1002/jso.25764
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous adenocarcinoma of the colon and rectum: A genomic analysis

Abstract: Background and Objectives Mucinous adenocarcinoma is a distinct subtype of colorectal cancer (CRC) with a worse prognosis when compared with non‐mucinous adenocarcinoma. The aim of this study was to compare somatic mutations and copy number alteration (CNA) between mucinous and non‐mucinous CRC. Methods Data from The Cancer Genome Atlas‐colon adenocarcinoma and rectum adenocarcinoma projects were utilized. Mucinous and non‐mucinous CRC were compared with regard to microsatellite status, overall mutation rate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…When small bowel tumors were excluded, restricting the analysis to the two most common peritoneal tumors (colon, appendix), a mutation burden of >1 remained associated with decreased survival. The detection of multiple mutations may be a potential surrogate for the level of cellular chaos yielding a more aggressive, refractory phenotype 31,32 . Currently, hotspot gene platforms are the most common panel, but further expansion of these panels combined with chromosomal and methylation analysis may help develop powerful and discriminatory tools for outcome and selection of best therapies 33,34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When small bowel tumors were excluded, restricting the analysis to the two most common peritoneal tumors (colon, appendix), a mutation burden of >1 remained associated with decreased survival. The detection of multiple mutations may be a potential surrogate for the level of cellular chaos yielding a more aggressive, refractory phenotype 31,32 . Currently, hotspot gene platforms are the most common panel, but further expansion of these panels combined with chromosomal and methylation analysis may help develop powerful and discriminatory tools for outcome and selection of best therapies 33,34 …”
Section: Discussionmentioning
confidence: 99%
“…However, the primary tumors were not available for testing in this study, and the omental implants were yielding a more aggressive, refractory phenotype. 31,32 Currently, hotspot gene platforms are the most common panel, but further expansion of these panels combined with chromosomal and methylation analysis may help develop powerful and discriminatory tools for outcome and selection of best therapies. 33,34 The association of TP53 and SMAD4 with poor survival was observed across all three high-grade tumor categories with peritoneal metastasis.…”
Section: Rate Of Actionable Mutationsmentioning
confidence: 99%
“…Previous studies have suggested that the genetic origin of mucinous colorectal adenocarcinoma is related to the BRAF, microsatellite instability (MSI), and CpG island methylation phenotype (CIMP) pathways. 7,8 There are differences in the expression of mucin family members in MC: MUC2 and MUC5 are highly expressed, whereas MUC1 shows low expression. The differential expression of mucin is related to the risk of metastasis and death.…”
Section: Introductionmentioning
confidence: 99%
“…Overall survival was poor especially for small-cell neuroendocrine carcinomas [25]. Comparing with non-mucinous adenocarcinoma, mucinous adenocarcinoma was a distinct subgroup of colon cancer with a worse prognosis [26]. Thus, instead of affecting our current results, it indicated that we achieved quite good results.…”
Section: Discussionmentioning
confidence: 58%